2021
DOI: 10.3390/en14185691
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Optimization of Electrical Discharge Coatings Using Conventional Electrodes

Abstract: An emerging topic is electrical discharge (ED) coating with its application on complex shapes and cavities to repair components or act as functional coatings. Because it is a variant process of an electric discharge machine (EDM) with the ability to coat on electrically conductive substrates, there is a possibility that next-generation electrical discharge machining components may exploit the attachment phenomenon to enhance recast layer properties. Previously, researchers have obtained ED coating by mixing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The three levels of EDM machining process parameters selected are shown in Table 2 . Output parameters such as surface quality, surface topography and homogeneity of the coatings rely on the input process parameters, viz., current, Ton, Toff and temperature, as shown in Table 2 [ 19 ]. Taguchi L9 design was followed to prepare the combination of parameters [ 30 , 31 ] as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three levels of EDM machining process parameters selected are shown in Table 2 . Output parameters such as surface quality, surface topography and homogeneity of the coatings rely on the input process parameters, viz., current, Ton, Toff and temperature, as shown in Table 2 [ 19 ]. Taguchi L9 design was followed to prepare the combination of parameters [ 30 , 31 ] as shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This method consists of alternatives in the rows and attributes in the columns. The matrix format can be expressed as follows [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers developed a hard carbide layer using multi-layer electrodes. Maddu J et al [34] reported a 20 μm thick copper coating with a conventional copper electrode and optimized the process parameter with grey relational analysis, and the result shows micro-cracks, coating thickness, and material deposition increases with the increase in current and pulse duration. Muralidharan B et al [35] experimentally investigate electric discharge deposition using a solid electrode with magnetic field, and the results show deposit increased by magnetic field effect.…”
Section: Electric Discharge Coating Processmentioning
confidence: 99%
“…Importantly, the characteristics of coatings on electrode surfaces wield substantial influence over machined surface topography after EDM, with grain size playing a pivotal role in determining indentation size [27]. In parallel, the interplay of technological parameters such as U, I, and Ton on quality indicators in EDM with coated electrodes requires thorough elucidation for the practical application of this technology [28].…”
Section: Introductionmentioning
confidence: 99%